2020
DOI: 10.3389/fpsyt.2019.00923
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Abnormities of Amygdala and Prefrontal Cortex in Major Depressive Disorder With Suicide Attempts

Abstract: Finding neural features of suicide attempts (SA) in major depressive disorder (MDD) may be helpful in preventing suicidal behavior. The ventral and medial prefrontal cortex (PFC), as well as the amygdala form a circuit implicated in emotion regulation and the pathogenesis of MDD. The aim of this study was to identify whether patients with MDD who had a history of SA show structural and functional connectivity abnormalities in the amygdala and PFC relative to MDD patients without a history of SA. We measured gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Study of Wang et al found that MDD patients with a history of SA had a reduced volume in the right and left amygdala and ventral, medial, dorsal PFC. These demonstrate the role of the amygdala and PFC in the pathogenesis of suicidal behavior and imply the amygdala-PFC circuit as a probable target for detection and prevention of suicidal behaviors [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study of Wang et al found that MDD patients with a history of SA had a reduced volume in the right and left amygdala and ventral, medial, dorsal PFC. These demonstrate the role of the amygdala and PFC in the pathogenesis of suicidal behavior and imply the amygdala-PFC circuit as a probable target for detection and prevention of suicidal behaviors [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In people diagnosed with BP who have attempted suicide, decreased FA has been observed in the fronto-occipital fasciculus, uncinate fasciculus, corpus callosum, internal and external capsule, corona radiata, and the thalamic radiations in comparison to those who have not attempted suicide. The presence of similar changes within the brain may indicate a common pathomechanism in these affective disorders [ 73 ]. Table 4 presents, inter alia, disturbances in diffusion parameters in various fiber bundles in affective disorders.…”
Section: Changes In White Matter In Affective Diseasesmentioning
confidence: 99%
“…Study of Wang et al found that MDD patients with a history of SA had a reduced volume in the right and left amygdala and ventral, medial, dorsal PFC. These demonstrate the role of the amygdala and PFC in the pathogenesis of suicidal behavior and imply the amygdala-PFC circuit as a probable target for detection and prevention of suicidal behavior [22].…”
Section: Discussionmentioning
confidence: 72%